Managing Capital Flows : Lessons From the Experience of Chile - Laurens, Bernard; Cardoso, Jaime (Washington, D.C. : International Monetary Fund, 1998)
As a result of the Asian crisis, methods of coping with volatile international capital markets have received considerable attention from observers and policymakers. It has been argued that the imposition by Chile of a nonremunerated reserve requirement on external borrowing played a useful role in the smooth liberalization of its capital account by allowing Chile to deal effectively with short-term capital inflows and thus to reduce its vulnerability to external shocks, and that such measures should be adopted by other countries. In light of this, this paper reviews Chile's experience in managing capital flows and draws lessons for policymakers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet